Combined laparoscopic colectomy and splenectomy for bleeding transverse colon cancer and MDS associated splenomegaly with refractory ITP - Bonatti, Hugo; Tang, Yong; Hamden, Hind (Digestive Medicine Research, 2020)
Splenectomy together with colectomy is most commonly performed as a result of iatrogenic injury and not as an additional elective procedure. A 72-year-old male patient presented with MDS associated ITP and splenomegaly and a bleeding colon cancer; combined laparoscopic splenectomy and transverse colectomy was offered. Access to the abdomen was achieved using the Fios 1st entry port in the right upper quadrant. Additional ports were placed and the abdomen was explored. Baseline platelet count was 4 K/mL. The very large spleen (25 cm in length) was mobilized by dividing the gastrocolic ligament and short gastric vessels followed by the lateral attachments and the splenocolic ligament. The omentum 10 cm proximal to the tumor in the distal transverse colon was transected. The splenic flexure and descending colon were completely mobilized followed by division of the mesentery at the base. The hilum at the lower pole was divided using an Echelon stapler but the main hilum was too bulky for safe laparoscopic division. A 10 cm epigastric incision was made and a wound protector placed. The rest of the tissue was divided using a hand assisted technique. The spleen was removed through the mini-incision, the colon was brought out and resected and anastomosed using a two staple load technique with a 75 mm GIA. Pathology demonstrated splenomegaly with signs of ITP and a T3N2 colon adenocarcinoma (known liver metastases). The patient had minor complications, was well at follow up but decided to withdraw care and expired after several weeks. Only few patients have an indication for elective splenectomy together with segmental colectomy. The combined procedure can be safely performed using a laparoscopic approach.